The universe. 4 : [videorecording (DVD)] : explore the edges of the unknown - Cohen, Douglas; Thompson, Erik, 1959- (A & E Television Networks : Distributed by New Video, 2007)
Gazing up from Earth, the Universe looks like a peaceful place where placid stars pass across the night sky. Could there be other intelligent life outside our solar system? The space suggests that the conditions for the life may not be unique to Earth. Over 13 billion years ago, from a point smaller than the size of a single atom the universe was born, and it continues to expand with every passing second.